Artifacts in behavioral research Robert Rosenthal and Ralph L. Rosnow's classic books - Rosenthal, Robert, 1933-; Rosnow, Ralph L. (New York ; Oxford : Oxford University Press, 2009)
This volume was designed as both introduction and reminder - an introduction to the topic for graduate students, advanced undergraduates and younger researchers, and a reminder to more experienced researchers, in and out of academia, that the problems of artifacts in behavioural research have not gone away.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Psychology -- Research; Social sciences -- Research